EFEKTIVITAS PENGGUNANAAN MODEL KOOPERATIF JIGSAW DALAM PEMBELAJARAN MENULIS PARAGRAF ARGUMENTASI PADA SISWA KELAS XI SMKN 1 RAWAMERTA - Fransiska Dewi, Shintia; Suprihatin, Dewi; Nuraini, Cut (Jurnal Ilmiah Wahana Pendidikan, 2024)
Education The current curriculum is student-centered and reflects pancasila, as is the Merdeka Curriculum (KURMER). This may be a good choice for you and your family to use with your own hands. The new research used by researchers is quantitative in this research using a similar experimental mode. The design has a control group, but it cannot function fully to control the outside variables that affect the carrying out of experiments. The class chosen by researchers in the xi MPLB 2 class as experiment class and xi to 5 as the control class chosen based on the ability of learners in the low category. The discussion of the results obtained from the research is a quantitative data of the pretest and posttest of experimental and control classes. Data obtained and analyzed using SPSS 29 for Windows. Having a maximum operating capacity of 95 and maximum control of 88, the sedan has a minimum mileage of 77, maximum deviation of 4,725 and 3,039. The reason for this analysis is that the information is different, and people who have the opportunity to use it have the right to use the menu to paraphrase arguments that are not included in the discussion.